Cellulose nanofiber lithium as well as preparation method and application thereof

By preparing cellulose nanofiber lithium (TOCNF-Li) binder, the problems of poor flexibility and swelling caused by PVDF binder in the prior art are solved, and a lithium-ion battery positive electrode with high mechanical strength and electrochemical performance are achieved.

CN119798470APending Publication Date: 2025-04-11QINGHAI UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411977964.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the prior art, the positive electrode sheet is coated with an oily PVDF binder, which has problems such as poor flexibility and prone to swelling in the electrolyte, which affects the electrochemical performance of the battery.

Method used

Cellulose is oxidized by 2,2,6,6-tetramethylpiperidine (TEMPO) and ultrasonication, and the cellulose is peeled into a single dispersed cellulose nanofiber (TOCNF) and a functional carboxy group is introduced on its surface. Then, lithium ions are attached to the cellulose nanofibers through ion exchange to prepare a cellulose nanofiber lithium (TOCNF-Li) binder.

Benefits of technology

TOCNF-Li adhesive has the characteristics of spontaneously forming a network, providing good mechanical support and flexibility, improving the mechanical strength and electrochemical properties of the battery, reducing the polarization of the electrodes and improving the rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798470A_ABST
    Figure CN119798470A_ABST
Patent Text Reader

Abstract

The invention provides cellulose nanofiber lithium as well as a preparation method and application thereof, and the preparation method comprises the following steps: step 1, preparation of cellulose nanofiber: oxidizing cellulose by adopting 2, 2, 6, 6-tetramethyl piperidine oxide (TEMPO) and carrying out ultrasonic treatment, so that micron-sized cellulose is stripped into single dispersed cellulose nanofiber (TOCNF), and the single dispersed cellulose nanofiber (TOCNF) is obtained; functional carboxyl groups (-COOH) are introduced into the surface of the polymer; and step 2, preparation of cellulose nanofiber lithium: attaching lithium ions to the cellulose nanofiber through ion exchange to obtain the cellulose nanofiber lithium. The prepared cellulose nanofiber lithium (TOCNF-Li) binder has the characteristic of spontaneously forming a network in the freeze-drying process, can provide good mechanical support for a positive electrode material and a conductive agent, and improves the mechanical strength while meeting the flexibility. By forming an intercommunicated conductive network structure, transmission of electrons and ions in the positive plate is facilitated, and a high-performance electrode with high mass load and good flexibility can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of lithium batteries, and more specifically to cellulose nanofiber lithium and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries (LIBs) are widely used in portable electronic devices such as mobile phones and computers due to their excellent cycle performance, high energy density and high safety performance. Most of the current strategies focus on the synthesis and modification of positive and negative electrode materials, while relatively few studies have been conducted on key auxiliary materials, binders. Although the binder in the electrode accounts for a small proportion in the battery, it plays an important role in maintaining the stability of the electrode network structure, promoting the transport of electrons and ions, and ensuring the excellent cycle stability and rate performance of the battery as a whole.

[0003] For a long time, polyvinylidene fluoride (PVDF) has been one of the most commonly used binders in industrial batteries due to its good electrochemical stability and bonding properties. However, there are some problems with PVDF in practical applications. On the one hand, PVDF has poor electronic and ionic conductivity, which directly affects the performance of the battery. In addition, the lack of functionalized side chains can only rely on weak van der Waals forces to combine with active materials, and cannot provide sufficient bonding force. After long-term use, it will cause the electrolyte to decompose, the active material to fall off, and the electrode to undergo significant polarization and reduce the rate performance. On the other hand, PVDF requires the use of volatile and highly toxic (N-methylpyrrolidone) NMP as a solvent, which is easy to cause environmental pollution and is not conducive to recycling, which is contrary to the sustainability and environmental friendliness required by new battery technology.

[0004] As a new type of binder, water-based binder uses water as solvent and has the advantages of no pollution, low price, wide source and easy drying, which has attracted much attention. Among them, water-based binders such as carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR) and polyacrylic acid (PAA) have been widely used in the market. Recently, with the in-depth development of various new water-based binders, sodium alginate (SA), carboxymethyl chitosan (C-CTS), β-cyclodextrin (β-CD) and molecular-level designed conductive polymer binders have shown better performance than PVDF.

[0005] However, most of these binders are hard and brittle. When applied to flexible electrodes, they cannot meet both flexibility and mechanical strength requirements. In addition, due to the brittleness of the polymer, the electrode is prone to cracking during repeated bending, which seriously affects the rate performance of the battery during long-term cycling. Therefore, exploring multifunctional binders with excellent performance has become the best strategy to achieve high specific capacity, stable cycle life and excellent rate performance in LIBs positive electrodes. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide an aqueous binder for lithium-ion battery positive electrodes, so as to solve the problems of using oily PVDF binders to coat positive electrode sheets in the prior art, such as poor flexibility and easy swelling in the electrolyte, and to further improve the electrochemical performance of the battery.

[0007] The present disclosure provides a method for preparing cellulose nanofiber lithium, comprising:

[0008] Step 1, preparation of cellulose nanofibers: cellulose is oxidized by 2,2,6,6-tetramethylpiperidinium oxide (TEMPO) and subjected to ultrasound, so that micron-sized cellulose is peeled off into single dispersed cellulose nanofibers (TOCNF), and functional carboxyl groups (-COOH) are introduced on the surface of the TOCNF.

[0009] Step 2, preparation of cellulose nanofiber lithium: attach lithium ions to cellulose nanofibers through ion exchange to obtain cellulose nanofiber lithium. Specifically, the sodium carboxylate groups on the cellulose nanofibers are converted into lithium carboxylate groups through ion exchange. A portion of the additional lithium ions present on the binder can compensate for a portion of the lithium source loss during the battery cycle.

[0010] In some embodiments, in step 1, 2,2,6,6-tetramethylpiperidine oxide and NaBr are weighed and added to 200 mL of deionized water in sequence. After 2,2,6,6-tetramethylpiperidine oxide and NaBr are completely dissolved by stirring at 5-15° C., 1 g of crushed cellulose powder is added to the reaction system; after the cellulose is evenly dispersed, 5 mL of NaClO solution (active chlorine content is 6-14%) is added to the reaction system, and the pH of the reaction system is controlled at 9-11 by continuously dropping 0.5 mol / L NaOH solution. After reacting for 4-5 hours at a stirring speed of 500 r / min, the oxidized cellulose is filtered and washed with deionized water for 3 to 5 times to obtain oxidized cellulose; the oxidized cellulose is prepared into a slurry with a concentration of 0.5% using deionized water, and the oxidized cellulose is stripped into cellulose nanofibers (TOCNF) by ultrasonication at a power of 600 W for 30 minutes in an ice water bath.

[0011] In some embodiments, the mass ratio of NaBr to 2,2,6,6-tetramethylpiperidinium oxide is 10:1; NaOH is added to make the pH of the reaction system 10.

[0012] In some embodiments, in step 2, 1M HCl is first added to a cellulose nanofiber suspension with a solid content of 0.5%, the pH value is adjusted to 2, and the mixture is stirred for 6 hours; the cellulose nanofiber-H is then washed with 0.5M HCl, and then filtered with water until the pH value of the cellulose nanofiber slurry is 4; LiOH is then added to the cellulose nanofiber slurry, the pH value is adjusted to remain at 10, and the mixture is stirred at room temperature for 6 hours; the slurry is then dialyzed in water for 3 days until its pH reaches 7; finally, the 2 mg / mL cellulose nanofiber-Li slurry is ultrasonicated in an ice bath at 600 W for 15 minutes.

[0013] In some embodiments, washing the cellulose nanofiber-H with 0.5 M HCl comprises washing the cellulose nanofiber-H with 0.5 M HCl a plurality of times.

[0014] In some embodiments, the dialysis bag used for dialysis has a size of 1000-5000 Da.

[0015] The present disclosure also provides a cellulose nanofiber lithium, which is prepared according to the above-mentioned preparation method of the cellulose nanofiber lithium.

[0016] The present disclosure also provides the use of the above-mentioned cellulose nanofiber lithium as a binder in a lithium ion battery.

[0017] Compared with the existing technology, the present invention has the following beneficial effects:

[0018] 1. The prepared cellulose nanofiber lithium (TOCNF-Li) binder has the characteristic of spontaneously forming a network during the freeze-drying process, which can provide good mechanical support for the positive electrode material and the conductive agent, meet the flexibility and improve the mechanical strength.

[0019] 2. The raw materials are easily available and inexpensive, which is conducive to production; and using water as a solvent can not only avoid environmental pollution, but also reduce physical harm to industrial production personnel.

[0020] 3. This binder can form an interconnected conductive network structure in the positive electrode, which is beneficial to the transmission of electrons and ions in the positive electrode sheet, and can realize high-performance electrodes with high mass load and good flexibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1A It is a SEM image of TOCNF disclosed in the present invention;

[0022] Figure 1B is a SEM image of TOCNF-Li disclosed in the present invention;

[0023] Figure 2A schematic diagram of the structure of the positive electrode sheet assembled with the TOCNF-Li binder disclosed in the present invention;

[0024] Figure 3 CV curves of half cells assembled in Example 1 and Example 2 of the present disclosure;

[0025] Figure 4 The first cycle curve of the half-cell assembled in Example 1 and Example 2 of the present disclosure at a rate of 0.1C;

[0026] Figure 5 The half-cell assembled for Example 1 and Example 2 of the present disclosure has 400 cycle performance at 2C rate. DETAILED DESCRIPTION

[0027] The following embodiments may enable those skilled in the art to more fully understand the present disclosure, but do not limit the present disclosure in any way.

[0028] Unless otherwise stated, the materials, reagents, etc. used in the following examples can be obtained from commercial sources.

[0029] The preparation method of the binder cellulose nanofiber lithium provided in the present disclosure comprises the following steps:

[0030] Step 1, preparation of cellulose nanofibers: cellulose extracted from wheat straw: diameter 10-50μm, length 30-150μm (purchased from Hefei BASF Biotechnology Co., Ltd.), through 2,2,6,6-tetramethylpiperidinium oxide (TEMPO) oxidation and high-intensity ultrasound, the micron-scale cellulose is peeled off into single dispersed cellulose nanofibers (TOCNF), and functional carboxyl groups (-COOH) are introduced on its surface.

[0031] Step 2, preparation of cellulose nanofiber lithium: The sodium carboxylate groups on TOCNF are converted into lithium carboxylate groups by ion exchange. A portion of the additional lithium ions present on the binder can compensate for a portion of the lithium source loss during the battery cycle.

[0032] In some embodiments, in step 1, appropriate amounts of TEMPO and NaBr are weighed and added to 200 mL of deionized water in sequence. The mixture is fully stirred at 5-15°C using a magnetic stirrer. After TEMPO and NaBr are completely dissolved, 1 g of crushed cellulose powder is added to the reaction system. After the cellulose is evenly dispersed, 5 mL of NaClO solution is added to the system. The pH of the reaction system is controlled at 10 by continuously dropping 0.5 mol / L NaOH solution. After reacting for 4-5 hours at a stirring speed of 500 r / min, the oxidized cellulose is filtered and washed with deionized water for 3 to 5 times to obtain oxidized cellulose. The oxidized cellulose is prepared into a 0.5% slurry with deionized water (the best stripping effect). The oxidized cellulose is stripped into cellulose nanofibers (TOCNF) by ultrasonication at a power of 600 W for 30 minutes in an ice water bath. Figure 1A The prepared cellulose nanofiber suspension was stored in a refrigerator for later use.

[0033] In some embodiments, the mass ratio of NaBr to TEMPO is 10:1; NaOH is added to make the pH of the reaction system 9-11.

[0034] In some embodiments, in step 2, 1M HCl is first added to a TOCNF suspension with a solid content of 0.5%, the pH is adjusted to 2, and stirred for 6 hours. The TOCNF-H is then washed with 0.5M HCl, filtered with water, until the pH of the TOCNF slurry is about 4. LiOH is then added to the TOCNF slurry, the pH is adjusted to about 10, and stirred at room temperature for about 6 hours. The slurry is then dialyzed in water for 3 days until its pH reaches 7. Finally, a 2mg / mL TOCNF-Li slurry is sonicated in an ice bath at 600W for 15 minutes. The TOCNF-Li dispersion is stored at 4°C for use with a solid content of 1.5%.

[0035] In some embodiments, the addition of 0.5 M HCl washes may be repeated multiple times and in excess.

[0036] In some embodiments, in step 2, the ion-exchanged cellulose nanofibers are dialyzed in water for 3 days until the pH reaches 7, and the size of the dialysis bag is 1000-5000Da to obtain a functionally lithiated cellulose nanofiber (TOCNF-Li) binder. The dialysis time should be as long as possible to remove impurities on the surface of TOCNF-Li.

[0037] The present disclosure also provides an application of an aqueous binder, that is, an application of the above-mentioned cellulose nanofiber lithium (TOCNF-Li) in a lithium-ion battery.

[0038] The following description is given in conjunction with specific embodiments to provide a better understanding of the present disclosure.

[0039] Example 1

[0040] A method for preparing an aqueous lithium battery binder comprises the following steps:

[0041] 1. Preparation of cellulose nanofibers: Micron-sized cellulose is stripped into single dispersed cellulose nanofibers by TEMPO oxidation and high-intensity ultrasound, and functional carboxyl groups (-COOH) are introduced on the surface of the micron-sized cellulose nanofibers. The specific steps are as follows: weigh appropriate amounts of TEMPO and NaBr and add them to 200 mL of deionized water in turn. Stir the mixture thoroughly with a magnetic stirrer at 5-15°C. After TEMPO and NaBr are completely dissolved, add 1 g of crushed cellulose powder to the reaction system. After the cellulose is evenly dispersed, add 5 mL of NaClO solution (with an active chlorine content of 10%) to the system. The pH of the reaction system is controlled at 10 by continuously dropping 0.5 mol / L of NaOH solution. After reacting for 4-5 hours at a stirring speed of 500 r / min, filter the oxidized cellulose and wash it with deionized water for 3-5 times to obtain oxidized cellulose. The oxidized cellulose was prepared into a 0.5% slurry with deionized water (the best stripping effect), and the oxidized cellulose was stripped into cellulose nanofibers (TOCNF) by ultrasonic treatment at 600 W power for 30 min in an ice water bath. Figure 1A The prepared cellulose nanofiber suspension was stored in a refrigerator for later use.

[0042] Example 2

[0043] 1. Preparation of cellulose nanofiber lithium: The sodium carboxylate groups on TOCNF are converted into lithium carboxylate groups by ion exchange. A portion of the additional lithium ions on the binder can compensate for a portion of the lithium source loss during the battery cycle; the specific steps are: first, 1M HCl is added to a TOCNF suspension with a solid content of 0.5%, the pH value is adjusted to 2, and stirred for 6h. Then TOCNF-H is washed with 0.5M HCl, and then filtered with water until the pH value of the TOCNF slurry is about 4. Then LiOH is added to the TOCNF slurry, the pH value is adjusted to about 10, and stirred at room temperature for about 6 hours. Then, the slurry is dialyzed in water for 3 days until its pH reaches 7. Finally, 2mg / mL TOCNF-Li slurry is ultrasonicated in an ice bath at 600W power for 15min. The TOCNF-Li dispersion is stored at 4°C for use with a solid content of 1.5%. Figure 1B : is the SEM image of TOCNF-Li disclosed in the present invention.

[0044] 2. Prepare flexible LiFePO4 / acetylene black / TOCNF-Li composite electrode by vacuum filtration (such as Figure 2 As shown), LFP, acetylene black and homemade binder with a mass ratio of 8:1:1 were weighed and placed in 60 mL of aqueous solution, and then the slurry was poured into a high-speed blender and stirred for 10 min. The dispersed slurry was poured into a vacuum filtration bottle for filtration, and a water filter membrane with a pore size of 0.22 μm was used. The filtered filter membrane was removed and placed in a freeze dryer for drying, and then the dried positive electrode sheet was slowly peeled off from the filter membrane, pressed and cut, and transferred to a glove box for standby use.

[0045] Comparative Example 1

[0046] The commercial PVDF binder was dissolved in NMP, covered with plastic wrap and stirred evenly, and the composite electrode of LiFePO4 / acetylene black / PVDF was prepared by coating. LFP, acetylene black, and PVDF with a mass ratio of 8:1:1 were weighed, placed in a mortar and ground for 20 minutes, and then the positive electrode slurry was evenly coated on the aluminum foil using a 20μm square coater, and then the aluminum foil was placed in a vacuum drying oven and vacuumed, and kept at 120°C for 12 hours. The powder tablet press was used for tableting, and then the aluminum foil coated with the positive electrode was cut into a positive electrode sheet with a diameter of 12mm using a manual punching machine, and transferred to the glove box for use.

[0047] The positive electrode sheets assembled with the binders of the above-mentioned Example 1, Example 2, and Comparative Example 1 were subjected to electrochemical tests, specifically using electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV), and battery performance tests, and the electrochemical properties of different binders were analyzed. The EIS test was conducted using the Shanghai Chenhua electrochemical workstation. The test range was 0.01 to 1×10 5 Hz, with an amplitude of 0.01 V. Cyclic voltammetry was performed using an electrochemical workstation (Shanghai Chenhua Instrument Co., Ltd.) with a voltage setting of 1.2 V to 5 V and a scan rate of 0.01 mV s -1 .

[0048] like Figure 3The cyclic voltammetry (CV) curves of LFP positive electrodes using different binders are shown. The test results all show obvious redox characteristic peaks. The redox peak current density of TOCNF / LFP and TOCNF-Li / LFP positive electrodes is significantly higher than that of PVDF / LFP positive electrode, indicating that TOCNF / LFP and TOCNF-Li / LFP electrodes have higher electrochemical reaction activity and reaction rate. In addition, the cyclic voltammetry curve of TOCNF-Li / LFP positive electrode shows the most symmetrical and sharpest redox peak and a smaller voltage difference of the redox peak, which indicates that the electrode using TOCNF-Li binder has lower electrode polarization and more favorable electrode reaction kinetics than TOCNF and PVDF.

[0049] like Figure 4 The first charge and discharge curves of LFP electrodes using different binders at a rate of 0.1C. The negative electrode uses a lithium sheet as a control electrode, and the separator uses a commercial polyethylene (PE) separator purchased from Qinghai Beijie New Materials Technology Co., Ltd. It can be observed from the figure that the first discharge capacity of the battery assembled with commercial PVDF binder is 154mAh·g -1 , while the first discharge capacity of TOCNF binder is about 159 mAh g -1 The first discharge capacity of TOCNF-Li binder can reach 163 mAh g -1 This is mainly because the uniform network structure formed by the TOCNF-Li binder makes the lithium iron phosphate and acetylene black evenly dispersed and forms a good conductive network. Secondly, lithium ions are introduced into its surface functional groups, which not only increases the free-moving lithium ion content in the pole piece, but also provides Li + The diffusion path to the surface of active particles enhances the activity of electrochemical reactions and also accelerates the lithium ion transport on the electrode surface, thereby effectively improving the charge and discharge capacity of the battery.

[0050] like Figure 5The cycling performance of LFP electrodes with different binders at 2C rate for 400 cycles is shown in the figure. It can be observed from the figure that the discharge capacity of the LFP electrode using TOCNF as a binder is higher than that of PVDF during the cycle. After 400 cycles, the discharge capacity of TOCNF is still 135mAh / g, corresponding to a capacity retention rate of 85.6%. It can be seen that the cycle stability of TOCNF is better than that of PVDF, and the discharge capacity is higher. The LFP electrode with TOCNF-Li as a binder was charged and discharged 400 times at 2C rate, with an initial capacity of 158.6mAh / g. After 400 cycles, the discharge capacity is still 147.9mAh / g, and its capacity retention rate can reach 93.2%. This is because the TOCNF-Li substrate not only constitutes a good conductive network, which is conducive to electron transmission, but also contains a part of lithium ions in the functional groups on the surface of the binder, which accelerates the deintercalation of lithium ions, reduces the capacity decay during the cycle, and improves the cycle stability.

[0051] The present disclosure provides a new type of environmentally friendly aqueous binder for lithium battery positive electrode materials, which has the characteristics of an interpenetrating network structure and provides sufficient mechanical support and good flexibility for the electrode. The binder disclosed in the present disclosure is cellulose extracted from wheat straw. The cellulose is peeled off into single dispersed cellulose nanofibers (TOCNF) through 2,2,6,6-tetramethyl-1-piperidinium oxide (TEMPO) oxidation and high-intensity ultrasound. The TOCNF is further functionally lithium-modified by ion exchange, and finally the performance-enhanced cellulose nanofiber lithium (TOCNF-Li) is obtained, which is used as a binder for the LiFePO4 positive electrode. Since the binder has good adhesion to the active material, it helps to improve the cycle stability of the battery. In addition, TOCNF-Li has a good effect on increasing Li + content, opening up new opportunities for Li + transmission pathway, thereby increasing the battery's Li + Diffusion efficiency and charge-discharge performance.

[0052] Those skilled in the art will appreciate that the above embodiments are merely exemplary embodiments and that various changes, substitutions, and alterations may be made without departing from the spirit and scope of the present disclosure.

Claims

1. A method for preparing cellulose nanofiber lithium, characterized in that: include: Step 1, preparation of cellulose nanofibers: cellulose is oxidized by 2,2,6,6-tetramethylpiperidinium oxide (TEMPO) and subjected to ultrasound, so that micron-sized cellulose is peeled off into single dispersed cellulose nanofibers (TOCNF), and functional carboxyl groups (-COOH) are introduced on the surface of the TOCNF. Step 2, preparation of cellulose nanofiber lithium: attaching lithium ions to cellulose nanofibers through ion exchange to obtain cellulose nanofiber lithium.

2. The method for preparing cellulose nanofiber lithium according to claim 1, characterized in that: In step 1, 2,2,6,6-tetramethylpiperidine oxide and NaBr are weighed and added to 200 mL of deionized water in sequence. After 2,2,6,6-tetramethylpiperidine oxide and NaBr are completely dissolved by stirring at 5-15° C., 1 g of crushed cellulose powder is added to the reaction system. After the cellulose is evenly dispersed, 5 mL of NaClO solution with an active chlorine content of 6-14% is added to the reaction system. The pH of the reaction system is controlled at 9-11 by continuously dropping 0.5 mol / L NaOH solution. After reacting at a stirring speed of 500 r / min for 4-5 hours, the oxidized cellulose is filtered and washed with deionized water for 3-5 times to obtain the oxidized cellulose. The oxidized cellulose is prepared into a slurry with a concentration of 0.5% by using deionized water. The oxidized cellulose is exfoliated into cellulose nanofibers (TOCNF) by ultrasonication at a power of 600 W for 30 minutes in an ice water bath.

3. The method for preparing cellulose nanofiber lithium according to claim 2, characterized in that: The mass ratio of NaBr to 2,2,6,6-tetramethylpiperidinium oxide is 10:1; NaOH is added to make the pH of the reaction system 10.

4. The method for preparing cellulose nanofiber lithium according to claim 1, characterized in that: In step 2, 1M HCl was first added to a cellulose nanofiber suspension with a solid content of 0.5%, the pH value was adjusted to 2, and the mixture was stirred for 6 hours; the cellulose nanofiber-H was then washed with 0.5M HCl, and then filtered with water until the pH value of the cellulose nanofiber slurry was 4; LiOH was then added to the cellulose nanofiber slurry, the pH value was adjusted to 10, and the mixture was stirred at room temperature for 6 hours; the slurry was then dialyzed in water for 3 days until its pH reached 7; finally, the 2 mg / mL cellulose nanofiber-Li slurry was ultrasonicated in an ice bath at 600 W for 15 minutes.

5. The method for preparing cellulose nanofiber lithium according to claim 4, characterized in that: Washing the cellulose nanofiber-H with 0.5M HCl includes washing the cellulose nanofiber-H with 0.5M HCl for multiple times.

6. The method for preparing cellulose nanofiber lithium according to claim 4, characterized in that: The size of the dialysis bag used for dialysis is 1000-5000Da.

7. A cellulose nanofiber lithium, characterized in that: The cellulose nanofiber lithium is prepared according to the preparation method of cellulose nanofiber lithium according to any one of claims 1 to 6.

8. Use of the cellulose nanofiber lithium according to claim 7 as a binder in lithium ion batteries.